The Kinetic responses and foraging behavior of Drosophila melanogaster larvae (Baghdad Science Journal, 2007)
Adaptive responses in larval behavior may be of two kinds: Taxis: This involves a change in direction relative to source of a stimulus. Kinesis: Kinesis has no directional component, but involves change in the rate of performance in response to a stimulus. Drosophila larvae exhibited flexible behavioral responses associated with food acquisition and selection for different environmental conditions. In this investigation, we are concerned explosively with kinetic responses to food viability. Third instar larvae were subjected to test for thirty minutes in each of the following conditions i) in distilled water, ii) in Ringer's solution, iii) in glucose solution and on live yeast suspension. In each case the larva was in a thin layer of solution, or suspension over agar gel. On non – nutritive substrates, such as distilled water the predominant behavior is locomotion accompanied by exploratory movements foraging for food. When food is encountered the predominant behavior shifts from locomotion to feeding by sustained rhythmic scooping with the mouth hooks. Locomotore activity remains constant on yeast but immediately rises on transfer to Ringer's solution over the observation period. This is orthokinesis. On transfer to glucose solution larvae again show the instant rise in locomotion, but remains at a constant level with no evidence of an orthokinetic response. Feeding activity rate remains constant on yeast whereas in Ringer's solution we observe another kinetic response, for which we propose the term fagokinesis. This response is not observed when larvae were transferred to glucose solution.